Cost effectiveness of a combination of instruments for global warming: A quantitative approach for Spain - M. C. Gallastegui; M. González-Eguino; I. Galarraga (SERIEs - Journal of the Spanish Economic Association, 2012)
Climate change is an important environmental problem and one whose economic implications are many and varied. This paper starts with the presumption that mitigation of greenhouse gases is a necessary policy that has to be designed in a cost effective way. It is well known that market instruments are the best option for cost effectiveness. But the discussion regarding which of the various market instruments should be used, how they may interact and what combinations of policies should be implemented is still open and very lively. In this paper we propose a combination of instruments: the marketable emission permits already in place in Europe for major economic sectors and a CO2 tax for economic sectors not included in the emissions permit scheme. The study uses an applied general equilibrium model for the Spanish economy to compute the results obtained with the new mix of instruments proposed. As the combination of the market for emission permits and the CO2 tax admits different possibilities that depend on how the mitigation is distributed among the economic sectors, we concentrate on four possibilities: cost-effective, equalitarian, proportional to emissions, and proportional to output distributions. Other alternatives to the CO2 tax are also analysed (tax on energy, on oil and on electricity). Our findings suggest that careful, well designed policies are needed as any deviation imposes significant additional costs that increase more than proportionally to the level of emissions reduction targeted by the EU.
Keywords: D58; H21; 330; environmental policy instruments; applied general equilibrium models; cap and trade; CO2 tax; Climate policy; Klimawandel; Ökosteuer; Emissionshandel; Soziale Kosten; Allgemeines Gleichgewicht; Spanien